2016
DOI: 10.1515/zkri-2016-1990
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and computational study of t-butyl N-[3-hydroxy-1-phenyl-4-(pyridin- 2-ylsulfanyl)butan-2-yl]carbamate and its pyrimidin-2-yl analogue

Abstract: The crystal structure analysis of the biologically-relevant title compound (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…As part of our ongoing structural studies of compounds having biological activities [35][36][37][38], some of us have reported the structures of 2-oxo-2H-chromene-3-carboxamides, 1, see Figure 1 [39,40]. These studies, and a survey of related compounds in the CCDC data base, indicated the near planarity of such molecules arising from the very strong classical intramolecular N-H • • • O hydrogen bond, involving the amido group and the chromene carbonyl oxygen atom, which essentially fixes the overall conformation to be near planar, see Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our ongoing structural studies of compounds having biological activities [35][36][37][38], some of us have reported the structures of 2-oxo-2H-chromene-3-carboxamides, 1, see Figure 1 [39,40]. These studies, and a survey of related compounds in the CCDC data base, indicated the near planarity of such molecules arising from the very strong classical intramolecular N-H • • • O hydrogen bond, involving the amido group and the chromene carbonyl oxygen atom, which essentially fixes the overall conformation to be near planar, see Figure 1.…”
Section: Introductionmentioning
confidence: 99%